Genetic variations of filaggrin encoding gene \((FLG)\) in the Vietnamese population revealed from whole-exome sequencing - Nhung, Vu Phuong; Giang, Nguyen Huong; Hong Nhung, Nguyen Thi; Ton, Nguyen Dang; Ha, Nguyen Hai (Academia Journal of Biology, 2022)
Filaggrin is a key protein that facilitates terminal differentiation of the epidermis and maintains skin barrier function. Mutations in the gene encoding filaggrin (FLG) have been identified to cause ichthyosis vulgaris, increase the risk of atopic dermatitis and other skin diseases. In this study, we established the database of FLG gene obtained by whole-exome sequencing (WES) of 244 Vietnamese. We also estimated allele and genotype frequencies of the FLG gene in this Vietnamese population and predicted the impact of novel variants on protein function using in silico analysis tools. The detected variants included 126 nonsynonymous, six nonsense mutations, six frameshift insertions/deletions, and one non-frameshift deletion, mostly located in exon 3. Of which, there were 11 novel variants have been identified and four of them were predicted as detrimental for encoding protein. Remarkable pathogenic variants were mostly nonsense variants, showing the main genetic factor underlying the pathology of diseases caused by FLG. The results obtained in this study would provide essential information about the genetic characteristics of FLG in the Vietnamese population and the risk of occurrence of diseases related to this gene, which facilitates the development of new specific and accurate diagnosis, treatment, and prevention options for FLG-related diseases, particularly in Vietnamese.